Pengaruh Work Family Conflict dan Psychological Well-Being Terhadap Burnout pada Pegawai Negeri Sipil (PNS) Wanita di Organisasi “X” Wilayah Jawa Tengah dan Daerah Istimewa Yogyakarta - Astuti, Beti Ari; D.S, Triana Noor Edwina; Fitriana , Nina (Publikasi Indonesia, 2025)
Work family conflict and psychological well-being are important factors affecting burnout among female employees with dual roles. This study aims to determine the effect of work family conflict and psychological well-being on burnout among female civil servants at the Customs Organization of Central Java and Special Region of Yogyakarta. The research method used a quantitative approach with purposive sampling technique on 108 married female civil servant respondents. Research instruments used the Maslach-Trisni Burnout Inventory (M-TBI), Greenhaus & Beutell's Work Family Conflict scale, and Ryff's Psychological Well-Being scale. Data analysis used multiple linear regression with IBM SPSS 22.0. Results showed that simultaneously work family conflict and psychological well-being significantly affected burnout (R² = 0.398; p < 0.001). Partially, work family conflict had a significant positive effect on burnout (β = 0.291; p = 0.007), while psychological well-being had a significant negative effect on burnout (β = -0.393; p < 0.001). These findings indicate the importance of organizational support in managing work-family balance and improving psychological well-being to prevent burnout among female employees.